Behavior of Castellated Beams with and Without Stiffeners (International Journal of Innovative Research in Computer Science & Technology, 2020)
Castellated beam applications for diverse  buildings are quickly gaining popularity. This is a result of  the section's enhanced depth without adding weight,  excellent strength-to-weight ratio, low maintenance  requirements, and low cost of painting. Increased vertical  bending stiffness, ease of service provision, and appealing  appearance are the main advantages of castellated beams.  Castellated beams are made by zigzaggingly cutting I  sections, then rejoining them to increase the depth of the  parent I sections. When castellated beams are loaded, their  increased depth makes them more susceptible to web post  buckling and lateral torsional buckling failure. There are  numerous other forms of failure that must be considered,  such as the development of flexure mechanisms, lateral  torsional buckling, and vierendeel mechanisms, rupture of  the welded joint in a web post, and shear buckling of a web  post. A study demonstrates how using stiffeners in the  beam's web part can reduce these failures. Therefore, it is  necessary to do a thorough analysis of the stiffeners'  number, size, and readily available places in the web part of  the castellated beam. In order to explore the experimental  and analytical behavior of the castellated beam with  stiffeners, an attempt has been undertaken in the current  paper. The outcome shows that using end stiffeners at the  ends of castellated beams increases their strength and  reduces their deflection.
Keywords: Raw Water; Disinfection; Pathogens; Chlorine by Products and Distribution System